The ANALISIS PERBANDINGAN PERKUATAN DINDING PENAHAN TANAH DENGAN SHEET PILE - Trisno Lestari, Rini; Herzanita Y, Ayu; Zuhdan, Muhammad Ghinva (Politeknik Negeri Jakarta, 2025)
Natural disasters are recurring challenges experienced by countries worldwide, including Indonesia. One of the most common natural disasters in Indonesia is landslides, which frequently occur in various regions each year. Soil plays a critical role in construction, as stable and strong soil conditions are essential for structural integrity. However, poor soil conditions are often encountered, particularly on sloped terrain, increasing the risk of landslides. This study aims to analyze the Safety Factor (SF) of a slope using software based on the Limit Equilibrium Method (LEM). The SF value serves as a reference for further analysis; when SF < 1, reinforcement is required to support the applied loads. The slope stability analysis in this study yielded an SF value of 0.52. Based on this result, two reinforcement methods were evaluated: Retaining Wall and Corrugated Concrete Sheet Pile (CCSP). The analysis indicated that the Retaining Wall failed to adequately support the slope. In contrast, the CCSP reinforcement provided sufficient stability, with a Safety Factor of 1.587. Therefore, the Corrugated Concrete Sheet Pile (CCSP) is recommended as a safe and effective slope reinforcement solution.